2012
DOI: 10.1155/2012/613403
|View full text |Cite
|
Sign up to set email alerts
|

A New Piezoelectric Actuator Induces Bone FormationIn Vivo: A Preliminary Study

Abstract: This in vivo study presents the preliminary results of the use of a novel piezoelectric actuator for orthopedic application. The innovative use of the converse piezoelectric effect to mechanically stimulate bone was achieved with polyvinylidene fluoride actuators implanted in osteotomy cuts in sheep femur and tibia. The biological response around the osteotomies was assessed through histology and histomorphometry in nondecalcified sections and histochemistry and immunohistochemistry in decalcified sections, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…In addition, recently developed thermoresponsive biomaterials using shape memory polymers can alternate morphology in response to physiologic temperatures once implanted [78]. Finally, electrically-conducting biomaterials are also well suited for bone tissue engineering, since it has been shown that electrical fields can promote bone healing and regeneration [81,82]. For more information about next generation biomaterials please refer to the reviews [83][84][85][86].…”
Section: Next Generation Biomaterialsmentioning
confidence: 99%
“…In addition, recently developed thermoresponsive biomaterials using shape memory polymers can alternate morphology in response to physiologic temperatures once implanted [78]. Finally, electrically-conducting biomaterials are also well suited for bone tissue engineering, since it has been shown that electrical fields can promote bone healing and regeneration [81,82]. For more information about next generation biomaterials please refer to the reviews [83][84][85][86].…”
Section: Next Generation Biomaterialsmentioning
confidence: 99%
“…Different techniques have been used to process PVDF and its polymer/composites based in different strategies (Table 1) to obtain various morphologies including micropillars [21], particles [20,22], films [23][24][25] and fibers [15,[26][27][28][29][30][31] in order to better suit specific tissue engineering strategies. Further, it has been shown that substrates based on PVDF have different influence on cell adhesion, proliferation and differentiation [7] depending on their morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Reis et al. () used the piezosurgery in orthopedic application. The study showed that the bone deposition rate was significantly higher in the mechanically stimulated areas.…”
mentioning
confidence: 99%